Challenges and Opportunities for Indonesian Environmental Management in The Industry 4.0 Era - Ayu Shinta Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The issuance of Law Number 11 of 2020 regarding Job Creation was welcomed by most business actors, but on the other hand it left concerns about the risk of massive environmental degradation. One of the efforts to synchronize the spirit of accelerating business licensing with environmental protection and management is the industrial framework 4.0. The form of Industry 4.0 which is integrated, agile , accurate, synchronized with each other, and encourages acceptance of new perspectives with virtual-digital aspects, enables innovation in the use of new methods in environmental management. So far the government of the Republic of Indonesia has prepared sufficient regulatory and institutional arrangements to accommodate the conceptual industry 4.0 into the challenges of sustainable environmental management. In carrying out the transformation of sustainable development from conventional concepts towards 4.0, human resources are needed who are able to see opportunities and build the required competencies.